Monetization Strategies of Chinese Knowledge Content Creators on Social Media Platforms - He Zhiming; Liu Xueying; Rong Lanqi; Wang Leyi (SHS Web of Conferences)
In recent years, the increasing audience of knowledge-based short videos in China has made the knowledge payment industry develop continuously. Therefore, it is helpful to analyze the monetisation mode of knowledge short video creators for the sustainable development of the industry. This paper collects and analyzes data from four different media platforms and finds that there are obvious differences in user groups and content preferences of different platforms. Moreover, short video bloggers on different platforms mainly choose different monetization modes. At the same time, private domain traffic is also an effective way for video creators to consider monetization. Finally, this paper will summarize the best monetization ways that knowledge short video creators on different platforms can take and the ways that can maintain the long-term attractiveness of the industry. For example, to ensure the quality of content and make innovations on this basis, to meet the diversified needs of users, to understand the preferences of users on different platforms and make adjustments. To ensure long-term credibility, bloggers need to be aware of the importance of private domain traffic.